2017
DOI: 10.14202/vetworld.2017.1066-1071
|View full text |Cite
|
Sign up to set email alerts
|

Pathology and immunohistochemistry study of Newcastle disease field case in chicken in Indonesia

Abstract: Aim:The aim of the study was to examine pathology and the distribution pattern of Newcastle disease virus (NDV) in internal organs of chickens from a field case using immunohistochemical staining.Materials and Methods:10 groups of broiler, layer, and domestic chicken were collected from necropsy room Division of Pathology, Bogor Agricultural University. These chickens were originated from West Java and collected based on pathologist diagnosis as suspect of Newcastle disease (ND). They were subsequently confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 20 publications
7
43
1
3
Order By: Relevance
“…In this study, the microscopic lesions showed hemorrhages and necrosis in the mucosa and submucosa of proventiculus, desquamation of proventriculus epithelial layer, globular destruction of proventiculas surface, hyperemia of the muscularis layer and infiltration of inflammatory cells to submucosal layer of proventriculus glands, intestinal villi were blunted and necrosis of sub mucosa and mononuclear cell infiltration in the lamina propria, decreased number of lymphocytes in periarterial lymphotic sheath of spleen, hemorrhages, congestion and necrosis in epithelial mucosal cell of spleen, degeneration and multifocal necrosis in liver of broiler chicken, while in layer chicken they were accompanied by perihepatitis, hemorrhage, necrosis, and multifocal inflammatory cell infiltration in liver, Congestion, edema, and mononuclear inflammatory infiltration at the inside and the wall of alveoli, epicarditis and myocarditis, myocardium degeneration of heart, congestion, hemorrhage, mononuclear inflammatory cell infiltration in subepithelial layer of trachea which have been already reported by Etriwati et al (2017), Brar et al (2017) and Pabitra et al (2016).…”
Section: Prevalence Of Nd In Vaccinated Chickens Having Specific Hi Asupporting
confidence: 63%
“…In this study, the microscopic lesions showed hemorrhages and necrosis in the mucosa and submucosa of proventiculus, desquamation of proventriculus epithelial layer, globular destruction of proventiculas surface, hyperemia of the muscularis layer and infiltration of inflammatory cells to submucosal layer of proventriculus glands, intestinal villi were blunted and necrosis of sub mucosa and mononuclear cell infiltration in the lamina propria, decreased number of lymphocytes in periarterial lymphotic sheath of spleen, hemorrhages, congestion and necrosis in epithelial mucosal cell of spleen, degeneration and multifocal necrosis in liver of broiler chicken, while in layer chicken they were accompanied by perihepatitis, hemorrhage, necrosis, and multifocal inflammatory cell infiltration in liver, Congestion, edema, and mononuclear inflammatory infiltration at the inside and the wall of alveoli, epicarditis and myocarditis, myocardium degeneration of heart, congestion, hemorrhage, mononuclear inflammatory cell infiltration in subepithelial layer of trachea which have been already reported by Etriwati et al (2017), Brar et al (2017) and Pabitra et al (2016).…”
Section: Prevalence Of Nd In Vaccinated Chickens Having Specific Hi Asupporting
confidence: 63%
“…Protein profile of no NDV-infected chicken embryos is more complex than the protein profile of NDV-infected chicken embryos of all different levels. According to Dewi and Surachmi [ 17 ] that there are many serine protease-containing enzymes such as trypsin in the AF of ECEs that were infected with NDV. The enzymes degrade specific proteins on the molecular weight so that the gel will not absorb color and will be visualized as a band that is not stained.…”
Section: Discussionmentioning
confidence: 99%
“…However, a different result was reported when using Salatiga isolate inoculated in the chicken embryo with congestion and hemorrhage in lungs together with congestion in intestines, liver, and heart (Putra et al, 2012). Other different results also found when the virus isolate inoculated into adult chickens, for example, a study in West Java discover pneumonia, pericarditis, myocarditis, catarrhal enteritis, and hepatitis (Etriwati et al, 2017) and in India using Genotype XIII of NDV shown necrosis, degeneration, hemorrhages, and mononuclear cell diffuse infiltration in visceral organs of adult chicken (Khorajiya et al, 2015). Susta et al (2015) prove using NDV genotype XIV (Niger/06 isolate) and genotype XVII (isolate of Nigeria/06 and BF/08) that obtain from West Africa which inoculate into adult chicken showing necrosis, dulling of villous, mucosal erosion, segmented hemorrhagic and the depletion of lymphoid in intestine together with minimal lesion in respiratory organ.…”
Section: Resultsmentioning
confidence: 91%
“…The viremia also proves that all organs that we observed in the embryo showing pathological lesions. That statement also stated by Etriwati et al (2017) whom state the velogenic type virus inoculate into adult chicken can be found in the vascular endothelial cells by using immunochemistry which means the virus can circulate through the vascular vessel and replicate in the endothelial vascular to create a circulation disorder.…”
Section: Resultsmentioning
confidence: 96%